2008
DOI: 10.1021/bm800200a
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge Structural Protein from the Jaws of Nereis virens

Abstract: The fang-like jaws of the marine polychaete Nereis Virens possess remarkable mechanical properties considering their high protein content and lack of mineralization. Hardness and stiffness properties in the jaw tip are comparable to human dentin and are achieved by extensive coordination of Zn 2+ by a histidine-rich protein framework. In the present study, the predominant protein in the jaw tip, NVjp-1, was purified and characterized by partial peptide mapping and molecular cloning of a partial cDNA from a jaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 55 publications
5
84
0
9
Order By: Relevance
“…Histidine is a common zinc and copper binding motif, and zinc is abundant in slug glue (Werneke et al 2007). Furthermore, the amino acid composition recalls the structure of the zinc-binding protein Nvjp-1a, which hardens the jaws of nereid worms (Broomell et al 2008). Nvjp-1a has 36% glycine and 27% histidine (Broomell et al 2008), which is similar to the 5’ end of the transcript for Asmp57a (45% gly and 21% his).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histidine is a common zinc and copper binding motif, and zinc is abundant in slug glue (Werneke et al 2007). Furthermore, the amino acid composition recalls the structure of the zinc-binding protein Nvjp-1a, which hardens the jaws of nereid worms (Broomell et al 2008). Nvjp-1a has 36% glycine and 27% histidine (Broomell et al 2008), which is similar to the 5’ end of the transcript for Asmp57a (45% gly and 21% his).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the amino acid composition recalls the structure of the zinc-binding protein Nvjp-1a, which hardens the jaws of nereid worms (Broomell et al 2008). Nvjp-1a has 36% glycine and 27% histidine (Broomell et al 2008), which is similar to the 5’ end of the transcript for Asmp57a (45% gly and 21% his). A similar proportion of glycine and histidine was found in spinalin, a protein implicated in strengthening the spines of cnidarian nematocysts (Koch et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3). Histidine, present at >10 mol.% levels in both squid beak and polychaete jaws, was less than 2 mol.% in the perisarc [1,4,7,8]. Another intriguing compound detected by the AA composition analysis was a broad peak at 40 min corresponding to glucosamine (Fig.…”
Section: Aa Analysis and Wide-angle X-ray Diffraction Of Aglaophenia mentioning
confidence: 94%
“…Both jaws have similar shapes and mechanical properties that resemble those of human dentin but without a similar reliance on mineral. Glycera jaws consist of melanin ($37 dry wt.%), protein ($50%), copper-based minerals and metal ions (up to 10%), whereas Nereis jaws are a composite of halogenated proteins (70-90% of the total dry mass) and metal ions [1,4,[6][7][8][9][10]. Melanin, which is usually associated with pigmentation, has significant load-bearing properties in Glycera jaw [2].…”
Section: Introductionmentioning
confidence: 99%
“…[60] Both Ala and Gly-rich motifs also exhibit resemblance to peptide sequences from the wing cuticles of migratory locusts, [64] oyster shell matrix proteins (Pinctada genus) [65] and chicken claw keratins. [66] Finally, His-rich SRT motifs exhibit similarity to His-rich proteins [67] of the King ragworm jaw (Nereis virens), another hard tissues made of sclerotized proteins that are mechanically reinforced via His-Zn coordination bonds [68][69][70] and dense covalent cross-linking. [71,72] Generally speaking, our combinatorial assay showed that Ala-rich and His-rich peptides exhibit the strongest homo-peptidic interactions and such interactions are pH-dependent, being weaker under acidic conditions and the strongest near neutral pH.…”
Section: Discussionmentioning
confidence: 99%